2015
DOI: 10.1299/transjsme.14-00463
|View full text |Cite
|
Sign up to set email alerts
|

Kansei-related assessment and its application to a design for steering wheel operation characteristics in a subjective force perception space

Abstract: Kansei-related assessment and its application to a design for steering wheel operation characteristics in a subjective force perception space Abstract Kansei engineering is a Japanese approach by which products and services are developed and improved with consumers' psychological feelings and needs incorporated into the design domain. This paper proposes a new Kansei evaluation method in which human perception properties in vehicle steering wheel operation are considered. The method does not involve considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The operability of a vehicle's steering wheel changes when the reaction force characteristics vary. Takemura et al reported that the subjective perceptual force obtained by psychophysical experiments correlated more with the steering wheel operability than the quantitative physical force measured by sensors [14]. Jones reported that the perceived force is affected by the physical characteristics of an object and the human psychophysical characteristics [15].…”
Section: Introductionmentioning
confidence: 99%
“…The operability of a vehicle's steering wheel changes when the reaction force characteristics vary. Takemura et al reported that the subjective perceptual force obtained by psychophysical experiments correlated more with the steering wheel operability than the quantitative physical force measured by sensors [14]. Jones reported that the perceived force is affected by the physical characteristics of an object and the human psychophysical characteristics [15].…”
Section: Introductionmentioning
confidence: 99%